2021
DOI: 10.1007/s11306-021-01828-w
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in LC–MS-based metabolomics for Alzheimer’s disease early detection: targeted approaches versus untargeted approaches

Abstract: Background Alzheimer's disease (AD) is one of the most common causes of dementia in old people. Neuronal deficits such as loss of memory, language and problem-solving are severely compromised in affected patients. The molecular features of AD are Aβ deposits in plaques or in oligomeric structures and neurofibrillary tau tangles in brain. However, the challenge is that Aβ is only one piece of the puzzle, and recent findings continue to support the hypothesis that their presence is not sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“…Despite these advantages, a single analytical platform approach still dominates the metabolomics field, which may be a contributing factor to an abundance of tenuous metabolomics research studies populating the scientific literature. It may also explain the low reproducibility seen across multiple clinical studies aimed at identifying disease biomarkers 42,54b . MS methods have faced a growing concern over reproducibility and the accuracy of metabolite identifications 47k .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these advantages, a single analytical platform approach still dominates the metabolomics field, which may be a contributing factor to an abundance of tenuous metabolomics research studies populating the scientific literature. It may also explain the low reproducibility seen across multiple clinical studies aimed at identifying disease biomarkers 42,54b . MS methods have faced a growing concern over reproducibility and the accuracy of metabolite identifications 47k .…”
Section: Discussionmentioning
confidence: 99%
“…We recently explored the reproducibility of metabolomics platforms by conducting a meta‐analysis of 24 pancreatic ductal adenocarcinoma (PDAC) metabolomics studies from the scientific literature 54b . The majority of these studies relied on a single analytical platform, either NMR or LC–MS, to identify potential biomarkers for PDAC.…”
Section: A Multiplatform Approach Addresses the Reproducibility Chall...mentioning
confidence: 99%
See 1 more Smart Citation
“…With the continuous improvements in the related technologies, LC- Frontiers in Pharmacology frontiersin.org Frontiers in Pharmacology frontiersin.org QTOF/MS has unequivocally become an established informative technique for metabolomics studies and has been utilized mostly (Khamis et al, 2017;Chaleckis et al, 2019). Previous studies have concluded that a vast number of metabolites studied using the LC-QTOF/MS platform could help shed light on alteration in the metabolic pathway in AD (Reveglia et al, 2021). Yet it is worth noting that, in this research, a total of 10 low molecular weight metabolites such as butanoic acid, citrulline, urea, cholesterol, and lactic acid were detected, and nine of which had not been identified by the LC-QTOF/MS method.…”
Section: Discussionmentioning
confidence: 99%
“…The essential role of targeted metabolomics as a translational approach for clinical purposes has been demonstrated in biomarker studies of challenging diseases, including cardiovascular disease, [ 19 ] cancer, [ 20 ] and Alzheimer's disease, [ 21 ] as well as response to drug therapy in AMD. [ 22 ] However, the plasma sample is often influenced by external variables, such as diet and lifestyle, and may only partially reflect the metabolic status that occurs in the retina and RPE/choroid layers.…”
Section: Introductionmentioning
confidence: 99%